ABNORMAL UTERINE BLEEDING IN WOMEN OF REPRODUCTIVE AGE - Sparić, Radmila M; Tomašević, Đina; Anđić, Mladen; Spremović Rađenović, Svetlana (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: Abnormal uterine bleeding is one of the most common health disorders in women of reproductive age. In addition, it represents a significant public health problem. The aim of this paper is to present the modern classification, as well as the basis for diagnosis and treatment of abnormal uterine bleeding.Methods: This paper presents data from publications selected from the MEDLINE database using a combination of keywords: “menstrual bleeding”, “abnormal uterine bleeding”, “PALM-COEIN classification”, “leiomyoma”, “endometrial polyp”, “adenomyosis”, “gynecological malignancies”, “coagulopathy”, “diagnostics of abnormal uterine bleeding”, and “treatment of abnormal uterine bleeding”. The collected data from the selected studies were used and presented in this review paper.Conclusion: In order to achieve a unique classification of abnormal uterine bleeding, a classification was adopted under the name/acronym PALM-COEIN. The causes listed in the first part of the acronym (PALM) have a pathological/anatomical cause in the reproductive organs that can be diagnosed using imaging techniques and/or histopathological examination. The causes listed in the second part of the acronym (COEIN) represent a group of dysfunctional disorders and they cannot be diagnosed using imaging  echniques.
Keywords: bleeding; uterus; menstrual cycle